EXPLOSIVE DETECTOR DESIGN TO KNOW THE EXISTENCE OF EXPLOSIVE MATERIALS BY COMPARING THE LARGE VALUE OF MEDNET MAGNET USING ARDUINO IN JUANDA AIRPORT AREA - Atmiasri; Gesang Fajar Rahmawan (BEST, 2020)
The design of this explosive detector is an alternative low-cost explosive detector device that can detect the presence of explosives by comparing the value of the magnetic field so that an object will be known to be an explosive or not. This tool can provide additional assistance in the Juanda airport area which still rarely uses conventional explosive detector equipment because the price is still expensive. This design uses a magnetometer sensor that can calculate the magnitude of the magnetic field in the explosives and will send analog inputs in the form of voltage values to the Arduino displayed with LCD media and sound from the buzzer so that the category of explosives can be detected.